Ethene Conversion at a Zeolite‐Supported Ir(I) Complex. A Computational Perspective on a Single‐Site Catalyst System. Issue 15 (17th June 2021) - Vummaleti, Sai V. C.; Genest, Alexander; Rösch, Notker
Abstract: Applying a quantum mechanics/molecular mechanics scheme involving DFT calculations, a model study of mechanisms for ethene transformations at zeolite‐supported Ir(I) complexes is presented and the results compared to those of recent experiments and previous work on the isostructural Rh(I) complexes. Starting from the 2‐ligand complex [Ir(C2 H4 )2 ] +, in the presence of H2, the ethene conversion mechanisms studied yield solely ethane while the dimerization to 1‐butene via either the Cossee‐Arlman (CA ) mechanism or the metallacycle (MC ) mechanism was determined to be kinetically too demanding. Therefore, turning to 3‐ligand models, the calculations showed that the diethyl complex [Ir(C2 H4 )(C2 H5 )2 ] + strongly favors ethene hydrogenation over dimerization (via a CA mechanism), with crucial activation free energies of 27 kJ mol −1 and 113 kJ mol −1, respectively. The alternative route to dimerization via a MC mechanism is also not operative because the C−C coupling barrier is higher by 30 kJ mol −1 (in absolute terms) than the hydrogen activation in the CA mechanism. Thus, when Rh is substituted by Ir, the computational results allowed to rationalize the experimentally determined switching from ethene dimerization to ethane formation due to the significantly higher calculated barrier, by ∼50 kJ mol −1 relative to Rh, of C−C coupling in the Ir system. The present study illustrates the advantage of describing the active site in a single site catalysis system, yet it also highlights the potential complexity of such systems as revealed by comparing 2‐ to 3‐ligand models as well as models with different metal centers, Rh vs Ir, in the light of conversion rates via the energetic span concept. Abstract : Single‐Site System : DFT modelling reveals a complex reaction network for single‐site, faujasite‐supported Ir(I) complexes with two or three organic ligands, exhibiting a preference for ethene hydrogenation over dimerization to butene, at variance from the analogous Rh system.